2009
DOI: 10.1111/j.1438-8677.2008.00183.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of lipoxygenase products and monoterpenes by tomato plants as an indicator of Botrytis cinerea‐induced stress

Abstract: Changes in emission of volatile organic compounds (VOCs) from tomato induced by the fungus Botrytis cinerea were studied in plants inoculated by spraying with suspensions containing B. cinerea spores. VOC emissions were analysed using on-line gas chromatography-mass spectrometry, with a time resolution of about 1 h, for up to 2 days after spraying. Four phases were delimited according to the starting point and the applied day/night rhythm of the experiments. These phases were used to demonstrate changes in VOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
68
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 40 publications
(39 reference statements)
8
68
2
Order By: Relevance
“…In our studies we found only (Z)-3-hexenol which is emitted from tomato under osmotic stress compared with the previous articles which reported four or even nine different C5 and C6 green leaf volatiles, respectively [21,16]. The emission became significant even at 100 mM NaCl in soil but was very low for control plants.…”
Section: The Influence Of Soil Salinity On Volatile Organic Compoundscontrasting
confidence: 65%
See 3 more Smart Citations
“…In our studies we found only (Z)-3-hexenol which is emitted from tomato under osmotic stress compared with the previous articles which reported four or even nine different C5 and C6 green leaf volatiles, respectively [21,16]. The emission became significant even at 100 mM NaCl in soil but was very low for control plants.…”
Section: The Influence Of Soil Salinity On Volatile Organic Compoundscontrasting
confidence: 65%
“…The emissions consisted of α-pinene, camphene, 2-carene, α-phellandrene, limonene, β-phellandrene, (E)-β-ocimene and terpinolene as have been previously reported by Jensen et al [21] and Copolovici et al [16]. The composition was the same for stressed and control plants and could be due to cellular damage or enhanced permeability of barriers of terpene-containing structures.…”
Section: The Influence Of Soil Salinity On Volatile Organic Compoundssupporting
confidence: 62%
See 2 more Smart Citations
“…Emissions of different compounds from the same plant exhibit different temporal responses to herbivory stress (Copolovici et al, 2011). Additionally, the plant stress response varies depending on the type of biotic stress and/or the type of plant; other studies have shown increases in total terpene emission rates after herbivory exposure with no change in the VOC profile (Jansen et al, 2009b;Priemé et al, 2000) or different responses of the same plant to pathogen vs. herbivory stress (Vuorinen et al, 2007). Finally, extrapolating these results to natural environments is further complicated where simultaneous exposure to multiple stressors is likely the rule rather than the exception; multiple abiotic and biotic stressors can interact to significantly alter the plant's response relative to any single stressor (Holopainen and Gershenzon, 2010;Trowbridge et al, 2014;Winter et al, 2012).…”
Section: Introductionmentioning
confidence: 99%